Faktor Prediktor Price Earning Ratio Perusahaan Sektor Pertanian Di BEI - Ida Ida; Nanirayani Sitanggang (Fakultas Ekonomi Universitas Islam 45, 2022)
The agricultural sector is a sector that is experiencing growth by the recording of 2.19% in the second quarter of 2020 even though Indonesia's economic development has a decline to negative 5.32%. The purpose of this study is to interpret whether the Current Ratio (CR), Debt to Equity Ratio (DER), and Return On Equity (ROE) can predict Price Earning Ratio (PER) in agricultural sector companies listed on the Indonesia Stock Exchange. The sampling method used was the purposive sampling method. There are 47 observations data were analyzed using multiple linear regression analysis. The test results prove that Return on Equity (ROE) is a positive and significant predictor of Price Earning Ratio (PER), but Current Ratio and Debt to Equity Ratio (DER) are not significant predictors of Price Earning Ratio (PER). Potential investors need to consider Return on Equity (ROE) in their investment decisions.